2007
DOI: 10.3324/haematol.11568
|View full text |Cite
|
Sign up to set email alerts
|

Mutation of SBDS and SH2D1A is not associated with aplastic anemia in Japanese children

Abstract: © F e r r a t a S t o r t i F o u n d a t i o n

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 9 publications
1
3
0
Order By: Relevance
“…The cases that carried this variant also exhibited low TERT expression and short TL and had poor response to IST which indicated that this variant may have a role in the pathogenesis of AA. In line with our results, the same findings were reported by Liang et al [ 26 ]. In contrast, Du et al and Yamaguchi et al [ 33 , 34 ] demonstrated that (G835A) has been reported also in control subjects with similar allelic frequency and concluded that c.835G>A was a SNP and unlikely to cause BMF.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…The cases that carried this variant also exhibited low TERT expression and short TL and had poor response to IST which indicated that this variant may have a role in the pathogenesis of AA. In line with our results, the same findings were reported by Liang et al [ 26 ]. In contrast, Du et al and Yamaguchi et al [ 33 , 34 ] demonstrated that (G835A) has been reported also in control subjects with similar allelic frequency and concluded that c.835G>A was a SNP and unlikely to cause BMF.…”
Section: Discussionsupporting
confidence: 94%
“…Polat et al [ 32 ] suggested that it might change the secondary mRNA structure of the transcript by folding the RNA. Different results were found by [ 26 ] who examined 96 AA patients and 76 healthy subjects in Japan and detected this variant in 59% of patients and 53% of controls. This higher prevalence might be attributed to the ethnic variability and the larger sample size studied.…”
Section: Discussionmentioning
confidence: 71%
“…Seventy‐nine Japanese children aged ≤15 years, referred to our institution between January 1990 and April 2011, were included in this study. Patients were excluded if they had paroxysmal nocturnal haemoglobinuria (PNH), exposure to toxic chemicals, chromosomal fragility, or mutations in TERC , TERT , SBDS or SH2D1A (Liang et al , ; Wang et al , ). Disease severity was classified based on the criteria of the International Aplastic Anaemia Study Group (Camitta et al , ; Bacigalupo et al , ).…”
Section: Patient Characteristicsmentioning
confidence: 99%
“…Similarly, the proportion of 141C>T change was different from the The proportions have been calculated out of total number of allele's screened. studies evaluating subjects from Canada, Latin America, Asia, and Japan (Table 2) [4,6,7]. The variation in the proportion of single nucleotide polymorphisms (SNPs) in different populations indicates the genetic heterogeneity of different ethnicities.…”
mentioning
confidence: 99%